Genetic changes in nonepithelial ovarian cancer. Issue 7 (July 2013) - Van Nieuwenhuysen, Els; Lambrechts, Sandrina; Lambrechts, Diether; Leunen, Karin; Amant, Frédéric; Vergote, Ignace
Nonepithelial ovarian cancers (OCs), including sex cord-stromal tumors (SCSTs) and germ cell tumors (GCTs), are an uncommon subset of OC, together accounting for 10% of all OCs. The etiology of these tumors remains largely unresolved. It is well established that tumorigenesis is the result of multiple genetic alterations driving a normal cell toward a malignant state. Much effort has been made into researching the molecular mechanisms underlying epithelial OC, but far less is known about the genetic changes in SCSTs and GCTs. Recently, a single point missense mutation (C134W) was found in the FOXL2 gene in approximately 95% of adult-type granulosa cell tumors, suggesting a key role for FOXL2 in these tumors. By contrast, the FOXL2 mutation was not found in the juvenile type. DICER1 somatic missense mutations were found in approximately 60% of Sertoli-Leydig tumors. Ovarian GCTs share many morphological features and a similar pattern of chromosomal alterations with testicular GCTs. In the latter, recent genome-wide association studies have identified seven susceptibility loci near KITLG, SPRY4, UKC2, BAK1, DMRT1, TERT and ATF7IP. All of the susceptibility loci detected thus far are all involved in primordial germ cell function or sex determination. TGF-β/BMP and Wnt/β-catenin signaling was absent in dysgerminomas, but present in yolk sac tumors, suggesting intertumoral heterogeneity. In this article, the authors aim to provide an overview of the current knowledge on the possible molecular changes in SCSTs and GCTs of the ovary.